2009
DOI: 10.1039/b821833a
|View full text |Cite
|
Sign up to set email alerts
|

Surprisingly high, bulk liquid-like mobility of silica-confined ionic liquids

Abstract: Mesoporous silica monoliths were prepared by the sol-gel technique and filled with 1-ethyl-3-methyl imidazolium [Emim]-X (X=dicyanamide [N(CN)2], ethyl sulfate [EtSO4], thiocyanate [SCN], and triflate [TfO]) ionic liquids (ILs) using a methanol-IL exchange technique. The structure and behavior of the ILs inside the silica monoliths were studied using X-ray scattering, nitrogen sorption, IR spectroscopy, solid-state NMR, and thermal analysis. DSC finds shifts in both the glass transition temperature and melting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
122
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 44 publications
13
122
1
Order By: Relevance
“…Functionalization [45] of silica matrix was also found to affect the phase behavior of confined IL. Gçbel et al [44] showed from DSC studies that in restrictive geometry, the melting point of [EMIM] based ILs decreases by~8 to 148C. Further, they found a shift in NMR peaks of bulk IL on confinement in pores.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Functionalization [45] of silica matrix was also found to affect the phase behavior of confined IL. Gçbel et al [44] showed from DSC studies that in restrictive geometry, the melting point of [EMIM] based ILs decreases by~8 to 148C. Further, they found a shift in NMR peaks of bulk IL on confinement in pores.…”
mentioning
confidence: 94%
“…The confinement of many ILs has been found to result in changes in the thermal properties (like melting point) as studied by differential scanning calorimetry (DSC). [41][42][43] Recently, Gçbel et al [44] have studied the DSC, NMR and IR spectra obtained from inserting 4 ] etc) in silica of different pore sizes, which was achieved by varying base catalysts like pyridine, 3-fluoropyridine and 2-picoline. More recently Gçbel et al [45] obtained IL-silica monoliths of different pore sizes by functionalizing the silica pore walls by adding N,N-dimethyl-pyridine-4-yl-(3-triethoxysilylpropyl)-ammonium iodide and 3-fluoropyridine and 2-(4-pyridylethyl)triethoxysilane in TMOS in different ratios.…”
mentioning
confidence: 99%
“…Due to the high polarity of silica particles, the dispersion of silica in silane included systems and controllability of the performance are far from satisfactory. Ionic liquid (IL), a kind of fascinating molten salt with nearly zero vapor pressure and high thermal stability [5][6][7], has demonstrated high affinity toward various kinds of solid, such as carbon nanotubes [8][9][10][11][12][13][14], silica [15][16][17] and clays [18]. Various interactions, including cation-π interaction [8][9][10][11]19], van der Waal forces [13], delocalized electron interaction [14] and hydrogen bonding [16,18] have been well acknowledged and therefore subjected to a plenty of applications [14,[16][17][18][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the effect of immobilization on the T m of [5,9,[12][13][14] in which a significant T m depression is also observed when ILs are immobilized or confined to the solid surfaces. However, the degree of depression in this work is lower than previously reported values, most likely due to the much larger diameter of the submicrospheres and different surface groups used in this study.…”
Section: Morphology Comparison and Phase Behavior Changementioning
confidence: 99%